2016
DOI: 10.1186/s40529-016-0147-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjacent land-use types on the distribution of soil organic carbon stocks in the montane area of central Taiwan

Abstract: BackgroundSoil organic carbon (SOC) stocks can be altered through reforestation and cropping. We estimated the effects of land use on SOC stocks after natural deciduous forests replaced by crops and coniferous plantations by examining the vertical distribution of SOC stocks at different depth intervals in an adjacent Oolong tea (Camellia sinensis L.) plantation, Moso bamboo (Phyllostachys pubescens) forest, Japanese cedar (Cryptomeria japonica) forest, and Taiwania (Taiwania cryptomerioides) forest in central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
1
15
3
Order By: Relevance
“…Following Aitkenhead’s regressive model, if the soil C/N ratio of Taiwan from Chen, et al . 35 is applied, the estimated DOC yield will be less than 10 kg-C ha −1 yr −1 , which is much lower than our observations. The large discrepancy between our observations with the two estimations through Ludwig and Aitkenhead’s work manifested the unusual DOC export in SMRs.…”
Section: Controlling Factors Of Doc Estimations In Smrscontrasting
confidence: 72%
See 1 more Smart Citation
“…Following Aitkenhead’s regressive model, if the soil C/N ratio of Taiwan from Chen, et al . 35 is applied, the estimated DOC yield will be less than 10 kg-C ha −1 yr −1 , which is much lower than our observations. The large discrepancy between our observations with the two estimations through Ludwig and Aitkenhead’s work manifested the unusual DOC export in SMRs.…”
Section: Controlling Factors Of Doc Estimations In Smrscontrasting
confidence: 72%
“…We further used our dataset on Aitkenhead-Peterson and McDowell 13 model that used soil C/N ratio as a dominant predictor for DOC yield. In Taiwan, the average SOC stock and soil C/N ratio are approximately 10–20 kg-C m −3 (see Table 1) and ~7–15 35 . Our SOC is similar to other forested mountainous regions; however, the soil C/N ratio is a little low in comparison with other systems worldwide indicating the N-enriched condition, likely due to the high N deposition, over 2000 kg-N km −2 24 and high mineralization of organic carbon in the acid soil 36 .…”
Section: Controlling Factors Of Doc Estimations In Smrsmentioning
confidence: 99%
“…Hence, further research is necessary. Land use change is identified as a cause of SOC losses through erosion and vegetation conversion, and has become a factor contributing to the increase in atmospheric CO 2 concentration [ 13 ]. The characteristics of SOC mineralization varied among different land use types, because the land use change could alter litterfall amount, litter chemistry and soil chemical and physical properties [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tea ( Camellia sinensis L.) is a perennial evergreen crop with root absorption characteristics and exudates. Tea plantations are artificially managed and gradually form a unique regional ecosystem [ 13 ]. Our previous studies showed that soil properties change with the increasing age of tea plantation, including the content of SOC and nutrient elements; these changed soil properties modify the soil structure and function [ 17 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, soil nutrients have been estimated at different scales, from field to global by geostatistical techniques [16]. Studies at different scales have determined that the main factors influencing the spatial variability of SOC and STN were soil types [23], climate [24,25], topography [26][27][28], land use patterns [29][30][31], tillage practices [1] and fertilizer application [32].…”
Section: Introductionmentioning
confidence: 99%